Sosialisasi Program Pendampingan Legalitas Usaha oleh Dinas Koperasi terhadap Pengembangan UMKM di Kecamatan Margorejo Kota Surabaya - Fauzan Ardiansyah; Wiwik Handayani (Universitas Pahlawan Tuanku Tambusai, 2026)
Limited understanding of business legality remains one of the main challenges faced by Micro, Small, and Medium Enterprises (MSMEs), restricting their access to financing, business partnerships, and various development programs. This community service program aimed to improve MSME owners' understanding of the importance of business legality through socialization and mentoring activities organized by the Department of Cooperatives in Margorejo District, Surabaya. The program was implemented through educational sessions, direct mentoring, observation, documentation, and discussions with participants. The results showed an improvement in participants' understanding of the benefits of business legality, particularly regarding the Business Identification Number (Nomor Induk Berusaha/NIB) and other supporting legal documents. Furthermore, participants were encouraged to complete their business legalization process formally. This program is expected to strengthen MSME competitiveness, expand access to business opportunities, and enhance the readiness of MSMEs to adapt to the digital economy.